Desain Produk Home Decor dari Material Paper Core Melalui Pendekatan Eksplorasi Material - Thaariq Abdullah; Edi Setiadi Putra (Jurnal Desain Produk Nasional, 2026)
The design of home decor products using paper core material is an innovative effort to create environmentally friendly and aesthetically pleasing items. Paper core, typically used as the inner core of paper rolls or other materials, holds significant potential for development into functional and decorative products. This material exploration approach aims to leverage the unique characteristics of paper core, such as strength, flexibility, and the ability to be processed through various techniques, including cutting, layering, and combining with other materials. This exploration involves testing various shapes, textures, and finishes on paper core to create home decor products that are not only visually appealing but also durable and sustainable. The resulting products aim to provide innovative design solutions for a market increasingly concerned with eco-friendly products. This approach emphasizes sustainability by reducing waste and utilizing materials with a more environmentally friendly lifecycle. This study aims to explore the potential of paper core as a primary material for creating home decor products that are not only aesthetically attractive but also functional and environmentally sustainable.